ДИТЯЧА ПЕРІОДИКА ЯК ЗАСІБ ФОРМУВАННЯ АКТИВНОГО ЧИТАЧА МОЛОДШОГО ШКІЛЬНОГО ВІКУ (Педагогіка вищої та середньої школи, 2022)
The article gives general description of the periodic for children and shows its role in the formation of an active reader of younger school age.